An emerging strategy: probiotics enhance the effectiveness of tumor immunotherapy via mediating the gut microbiome - Shuaiming Jiang; Wenyao Ma; Chenchen Ma; Zeng Zhang; Wanli Zhang; Jiachao Zhang (Gut Microbes, 2024)
ABSTRACTThe occurrence and progression of tumors are often accompanied by disruptions in the gut microbiota. Inversely, the impact of the gut microbiota on the initiation and progression of cancer is becoming increasingly evident, influencing the tumor microenvironment (TME) for both local and distant tumors. Moreover, it is even suggested to play a significant role in the process of tumor immunotherapy, contributing to high specificity in therapeutic outcomes and long-term effectiveness across various cancer types. Probiotics, with their generally positive influence on the gut microbiota, may serve as effective agents in synergizing cancer immunotherapy. They play a crucial role in activating the immune system to inhibit tumor growth. In summary, this comprehensive review aims to provide valuable insights into the dynamic interactions between probiotics, gut microbiota, and cancer. Furthermore, we highlight recent advances and mechanisms in using probiotics to improve the effectiveness of cancer immunotherapy. By understanding these complex relationships, we may unlock innovative approaches for cancer diagnosis and treatment while optimizing the effects of immunotherapy.